Differenzerfahrungen und deren künstlerischer Ausdruck in Collagen Am Beispiel Hannah Höchs - Staab, Lena Marie (Verlag Julius Klinkhardt, 2021)
"This dissertation examines the relationship between collage - experiences of difference - artists. It explores the (art) history of collage as well as the perspective on collage as an artistic, methodological, epistemological and biographical principle. Likewise, the thesis that experiences of difference materialize artistically as well as biographically and can be found in textual and pictorial material will be pursued - with a focus on subjectification theory. Experiences of difference are understood in this research as reflections of experiences of discrimination and of othering (processes of being made into supposed others). The present research on subjectification - which centers on the life and work of Hannah Höch (1889-1978) - is carried out, on the one hand, on the basis of a discourse-analytical examination of biographical text documents of the artist; on the other hand, this very text analysis is related to an image analysis of the höch collage "Lebensbild" from 1972/1973. The pictorial and textual material will be interrogated for the (de-)thematization of the four categories of difference: gender, class, body/disability, race as well as their intersectional entanglement. In a micro-linguistic fine analysis, the linguistic (re-)production of possible experiences of difference will be examined on the basis of the three analysis heuristics: invocation, self-statements, biographical experiences. Embedded in and engaging with contemporary discourses of art and special education, this work aims to transform research findings on experiences of difference/collage/artists for those same disciplines. The perspective of Hannah Höch as an artist has so far been a research desideratum with a deeper focus on the analysis of body/disability and gender; the present study addresses this very issue and thus also shows transdisciplinary connectivity to Gender and Disability Studies."